2021
DOI: 10.3389/fonc.2020.601175
|View full text |Cite
|
Sign up to set email alerts
|

Apatinib Plus Temozolomide: An Effective Salvage Treatment for Recurrent Glioblastoma

Abstract: BackgroundTreatment for recurrent glioblastoma is poor, and there is a need for better therapies. Here we retrospectively assessed the efficacy and toxicity of temozolomide plus apatinib, an oral small-molecule tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor 2 in recurrent glioblastoma.Materials and MethodsA retrospective analysis of patients with recurrent glioblastoma who underwent apatinib plus temozolomide treatment was performed. Apatinib was given at 500 mg once daily. Tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(32 reference statements)
1
4
1
Order By: Relevance
“…In this retrospective study, the ORR, the median PFS and OS were 52.6%, 5.1 months (95% CI, 4.5–5.7 months) and 10.4 months (95% CI, 6.3–14.5 months), respectively, which seemed to be better than the data of apatinib plus temozolomide for recurrent GBM in an observational study reported by Ge et al (2020) , with the ORR, the median PFS and the median OS were 26.3%, 4.9 months (95% CI, 2.8–7 months) and 8.2 months (95% CI, 6.9–9.5 months), respectively. Differing from previous studies mentioned above focusing on apatinib-based combination therapy, all patients in our study were treated with apatinib monotherapy, further suggesting the effectiveness of single-agent apatinib against recurrent/progressive GBM.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In this retrospective study, the ORR, the median PFS and OS were 52.6%, 5.1 months (95% CI, 4.5–5.7 months) and 10.4 months (95% CI, 6.3–14.5 months), respectively, which seemed to be better than the data of apatinib plus temozolomide for recurrent GBM in an observational study reported by Ge et al (2020) , with the ORR, the median PFS and the median OS were 26.3%, 4.9 months (95% CI, 2.8–7 months) and 8.2 months (95% CI, 6.9–9.5 months), respectively. Differing from previous studies mentioned above focusing on apatinib-based combination therapy, all patients in our study were treated with apatinib monotherapy, further suggesting the effectiveness of single-agent apatinib against recurrent/progressive GBM.…”
Section: Discussioncontrasting
confidence: 59%
“…Currently, only a few case reports, retrospective and prospective studies with small sample sizes indicated that apatinib might be effective in the treatment of recurrent glioma ( Wang et al, 2017 ; Zhang et al, 2017 ; Ding et al, 2018 ; Wang et al, 2019 ; Ge et al, 2020 ; Hui et al, 2021 ; Zhu et al, 2022 ). Hence, we conducted this retrospective study to provide more clinical evidence of apatinib as a salvage therapy in recurrent/progressive GBM patients.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective singlearm exploratory study including 15 recurrent glioblastoma patients thereafter yielded similar results, with a median PFS of 3.1 months and median OS of 8.7 months (17). These results were further confirmed in a retrospective analysis by Ge et al that showed a median PFS of 4.9 months and a median OS of 8.2 months (18). In addition, in a case report similar to ours, an adult with a brainstem anaplastic astrocytoma benefited from an initial treatment of combined radiotherapy, TMZ, and apatinib (500 mg/day) and had PFS of over 8 months (19).…”
Section: Discussionsupporting
confidence: 88%
“…[ 16 , 17 ] In a preclinical study, apatinib has the effect to suppress glioma cell proliferation and migration, and also to promote the anticancer effect of temozolomide. [ 18 ] Atinib treatment may be slightly toxic, resulting in anorexia (5.8%), hypertension (5.8%), thrombocytopenia (4.3%) and leucopenia (3.6%) in patients with grade III/ IV tumors. [ 18 ] Many of these toxic effects occur during early treatment and can be relieved by reducing the dose of apatinib and performing symptomatic management.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Atinib treatment may be slightly toxic, resulting in anorexia (5.8%), hypertension (5.8%), thrombocytopenia (4.3%) and leucopenia (3.6%) in patients with grade III/ IV tumors. [ 18 ] Many of these toxic effects occur during early treatment and can be relieved by reducing the dose of apatinib and performing symptomatic management. Our results suggested that treatment with apatinib and temozolomide is effective and might be better than single temozolomide treatment, specifically for cases with MGMT non-methylation.…”
Section: Discussionmentioning
confidence: 99%